2021
DOI: 10.4081/ijfs.2021.9031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beetroot (<em>Beta vulgaris</em>) extract on Black Angus burgers shelf life

Abstract: Beef burgers are meat preparations with easy perishability. To ensure a longer shelflife, the Regulation EU 1129/11 allows the use of some additives. However, healthconscious consumers prefer products which do not contain synthetic substances. Aim of the present study was to evaluate the effect of Red Beetroot (Beta vulgaris) integration on Black Angus made burgers shelf life. Red beet was prepared as powder and added to meat mixture as the same or in water solution. The study was split into 2 trials to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…In addition, it indicates that inadequate cleaning, unsatisfactory handling, and post-processing contamination from the polluted atmosphere around shops. The high prevalence of S. aureus in raw meat and handlers contain health hazards like toxin-mediated virulence and invasiveness to consumers [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it indicates that inadequate cleaning, unsatisfactory handling, and post-processing contamination from the polluted atmosphere around shops. The high prevalence of S. aureus in raw meat and handlers contain health hazards like toxin-mediated virulence and invasiveness to consumers [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that BCWE has high phenolic content and antioxidant capacity, it can be used as a natural antioxidant to control lipid oxidation in ground beef instead of synthetic antioxidants. The results obtained in the present study are similar to many studies showing that natural antioxidants such as plants, fruits and vegetables delay the oxidative deterioration in fresh meat and meat products 5–8,13–15,31–33,40 . In this regard, Ekici et al 41 demonstrated that black carrot concentrate (BCC) increased the antiradical activities and total phenolic content of Turkish dry‐fermented sausage samples.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with our findings, Turan and Şimşek 14 reported that the pH values of beef patties treated with black mulberry extract were lower than the control during 15 days of chilled storage in both aerobic and vacuum conditions. Similarly, a dose‐dependent decrease in pH values of fresh meat products incorporated with various vegetable extracts has been reported in previous studies 31–33 …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Natural preservatives have emerged as alternatives to synthetic preservatives [13]. Natural preservatives have shown potential to provide effective antimicrobial activity while reducing negative health effects.…”
Section: Introductionmentioning
confidence: 99%